Pore network of an Inceptisol under different uses and relativized S-index as an indicator of soil physical quality - Assis Júnior, Raimundo Nonato de; Mota, Jaedson Cláudio Anunciato; Freire, Alcione Guimarães; Alencar, Thiago Leite de (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate soil porous media quality under different uses, as well as to propose a new index to monitor changes in its structure due to management: the Srelative index. An Inceptisol under irrigated banana cultivation and secondary forest, in the Brazilian Apodi Plateau, was evaluated at three soil layers (0.0–0.1, 0.1–0.2, and 0.2–0.3 m) as to: particle size, particle and bulk density, organic matter content, intrinsic permeability to air, and water retention curve. Total porosity, index for pore continuity (defined by the ratio between soil intrinsic permeability to air and aeration porosity), volume of blocked pores, and the S and Srelative indices were determined. The Srelative index was calculated as the ratio between S-index values from undisturbed and disturbed samples of the same soil (Sundisturbed/Sdisturbed). Under the studied conditions, the Srelative index is a good quantifier of the changes imposed by soil use and management. Soil cultivation maintains or improves the quality of the evaluated attributes, except for blocked porosity, when compared with the soil under native secondary forest with ten years of regeneration after agricultural use.